Bleisure tourism and the impact of technology - Kumar, Narendra; Miranda-Fernandez, Karen; Santos, Vasco Ribeiro dos; Sharma, Swati (Advances in hospitality, tourism, and the services industry (AHTSI) book series, 2024)
In today's fast-paced world, professionals often struggle to balance their work commitments and personal well-being, particularly during business trips. The conventional approach to business travel usually prioritizes work over relaxation and exploration, leaving travelers feeling overwhelmed and burnt out. As a result, there is a growing need for a solution that allows individuals to seamlessly integrate work and leisure, fostering a healthier and more fulfilling travel experience. Bleisure Tourism and the Impact of Technology is a comprehensive reference source that explores the evolution and significance of bleisure tourism. It provides readers with valuable insights into how they can transform their business trips into enriching experiences. From practical strategies for blending professional commitments with leisure activities to case studies on successful bleisure destinations, this book equips readers with the knowledge and tools they need to embrace this transformative trend.